The impact of the implementation of management systems. Aspects to consider for decision making in organizations. Case of small and medium-sized enterprises in Bogota Colombia (2017)
The implementation processes management systems generate phenomena of resistance to change, which can affect decision making in organizations and the normal development of their activities. The eagerness to carry out processes of implementation of management systems without due internal analysis, from the products that affect the organizations, has generated disadvantages that affect the economic and organizational stability.